Platelet function testing: Current practice among clinical centres in Northern Europe. Issue 4 (5th May 2022) - Szanto, Timea; Zetterberg, Eva; Ramström, Sofia; Leinøe, Eva B.; Holme, Pål A.; Antovic, Jovan P.; Holmström, Margareta; Onundarson, Pall T.; Pikta, Marika; Vaide, Ines; Olsson, Anna; Magnusson, Maria; et al.
Abstract: Introduction: Platelet function tests are used to screen and diagnose patients with possible inherited platelet function defects (IPFD). Some acquired platelet dysfunction may be caused by certain drugs or comorbidities, which need to be excluded before testing. Aims: To identify current practice among centres performing platelet function tests in Northern Europe. Methods: A total of 14 clinical centres from Sweden (six), Finland (two), Denmark (two), Norway (one), Estonia (two) and Iceland (one) completed the survey questionnaire, the population capture area of about 29.5 million. Results: Six of the 14 (42.8%) centres providing platelet function assessment represent comprehensive treatment centres (EUHANET status). A Bleeding score (BS) or ISTH bleeding assessment tool (ISTH BAT score) is evaluated in 11/14 (78.6%) centres and family history in all. Five/14 centres (35.7%) use structured preanalytical patient instructions, and 10/14 (71.4%) recorded questionnaire on the preassessment of avoidance of any drugs or natural products affecting platelet functions. Preliminary investigations of screening tests of coagulation are performed in 10/14 (71.4%), while in 4/14 (28.6%), the diagnostic work‐up of IPFD and von Willebrand disease (VWD) is performed simultaneously. The work‐up of IPFD includes peripheral blood smear in 10/14 (71.4%), platelet aggregometry in all, flow cytometry in 10/14 (71.4%) and Platelet Function Analysis (PFA) in 3/11 (28.6%). Molecular genetic diagnosis is available in 7/14 (50%) centres. Conclusions: The considerable variability in the current practice illustrates the need for harmonization between the Northern European centres according to the international registers (i.e. EUHASS) and IPFD guidelines (ISTH, EHA).